EXAMINATION OF PRE-SERVICE CLASSROOM TEACHERS’ KNOWLEDGE ON THE FOUR OPERATIONS - Kubanç, Yasemin (ISMAIL HAKKI MIRICI, 2023)
The aim of this study was to examine pre-service classroom teachers’ knowledge on four operations. In this context, Algorithm Test (AT), Modelling Test (MT) and Additional Strategy Test (AST) developed by the researcher were used to examine the algorithm, modeling and additional strategy knowledge of the pre-service teachers. Thus, the pre-service teachers were expected to use different types of knowledge simultaneously. The solutions of the pre-service teachers were first classified as correct/incorrect, and then the solution stages were examined in detail. 110 pre-service classroom teachers at a state university in the 2021-2022 academic year participated in the study. Explanatory mixed method, in which quantitative and qualitative methods are used together, was adopted in the study. The explanatory design is known as a method in which quantitative data are supported by qualitative data. The quantitative data were collected using operation tests consisting 4 open-ended questions about four operations, and the qualitative data were collected through semi-structured interview technique. The results showed that the success order of the participants in all test types was addition, subtraction, multiplication and division, respectively. The success rate of the participants in AT and MT was above 50% while the success rate in the division in AST was below 50%. It was also found that the participants used seven different strategies and preferred to use only standard models in modelling. © 2014 by International Online Journal of Education and Teaching (IOJET).
Keywords: additional strategies; algorithm; four operations; modelling; prospective teachers